Physics and performances of III–V nanowire broken-gap heterojunction TFETs using an efficient tight-binding mode-space NEGF model enabling million-atom nanowire simulations. (29th May 2018) - Afzalian, A; Vasen, T; Ramvall, P; Shen, T-M; Wu, J; Passlack, M
Abstract: We report the capability to simulate in a quantum-mechanical atomistic fashion record-large nanowire devices, featuring several hundred to millions of atoms and a diameter up to 18.2 nm. We have employed a tight-binding mode-space NEGF technique demonstrating by far the fastest (up to 10 000 × faster) but accurate (error < 1%) atomistic simulations to date. Such technique and capability opens new avenues to explore and understand the physics of nanoscale and mesoscopic devices dominated by quantum effects. In particular, our method addresses in an unprecedented way the technologically-relevant case of band-to-band tunneling (BTBT) in III–V nanowire broken-gap heterojunction tunnel-FETs (HTFETs). We demonstrate an accurate match of simulated BTBT currents to experimental measurements in a 12 nm diameter InAs NW and in an InAs/GaSb Esaki tunneling diode. We apply our TB MS simulations and report the first in-depth atomistic study of the scaling potential of III–V GAA nanowire HTFETs including the effect of electron–phonon scattering and discrete dopant impurity band tails, quantifying the benefits of this technology for low-power low-voltage CMOS applications.